Optimizacija obratovanja verige hidroelektrarn na Spodnji Savi v času poplavnih dogodkov - Rak, Gašper (Acta hydrotechnica, 2019)
A complex combination of influencing factors and extensive planned interventions must be considered when planning hydropower production. In addition to electricity production, the main goal is conservation of the run-off regime and conservation or mitigation of flood risk in an affected area. Besides the design of interventions and structures important for HPP operating and other accompanying measures into aconsidered area, the appropriate operation of an individual HPP and HPPs chain as a whole contributes significantly to achievingthe desired goals during high waters.This paper presents an optimization of the HPP chain operation. on the section of Sava River between Radeče and state border with the Republic of Croatia. The approximately 60-km long, substantially urbanized section of the Lower Sava, where construction of achain of six run-of-the-river HPPsis in its finals stages, had to meet a number of requirements to improve or at least conserve the same level of flood risk and run-off regime on the border with the Republic of Croatia, defined by interstate agreement. In order to meet the requirements, we determined a uniform operating procedure of HPP chains during flood events that ensures the conservation of flood-wave characteristics along the chain of HPPs, while meeting the requirements of other stakeholders in this influential area. We showed with hydraulic analysis that the shape of the flood wave and its peak discharge can be conserved, but it is not possible to conserve natural flood-wave propagation time along the chain of HPPs.
Keywords: flood risk assessment; hidravlična analiza; HPP chain; hydraulic analysis; obratovanje; ocena poplavne ogroženosti; odtočne razmere; operation; run-off regime; veriga HE